The Grassland Fragmentation Experiment in the Swiss Jura Mountains: A Synthesis - Bruno Baur; Hans-Peter Rusterholz; Brigitte Braschler (Diversity, 2023)
We synthesize findings from a 7-year fragmentation experiment in species-rich, nutrient-poor, dry calcareous grasslands in the north-western Jura mountains, Switzerland. We used a standardized approach with 48 fragments (0.25–20.25 m2) and corresponding control plots in three sites. The 5-m-wide isolation area around the fragments was maintained by frequent mowing. Fragments experienced various ecological changes, e.g., plant biomass increased along fragment edges. We examined fragmentation effects on species richness and composition, abundance, genetic diversity, functional diversity, species traits and species interactions (pollination, herbivory, parasitism, disease) in a wide array of invertebrate (gastropods, spiders, woodlice, various insect groups) and plant taxa. Responses to fragmentation differed between taxonomical groups and species. While species richness and individual density were lower in fragments in some groups, the opposite was true for other groups. Fragmentation effects were most pronounced on species interactions; however, some effects only occurred with a delay. For example, fragmentation influenced foraging patterns of bumblebees, affecting pollination, which in turn resulted in a decreased outcrossing frequency and reduced genetic diversity in a focal plant species. We highlight key findings of the experiment and emphasize their implications for grassland conservation.